Management of Colorectal Cancer with Hepatic Metastasis - Hiranyakas, Art; Maipang, Tanaphon (The Bangkok Medical Journal, 2012)
Colorectal cancer has become one of the leading causes of cancer-related death worldwide. In Thailand, colorectal cancer (CRC) was the most commonly reported gastrointestinal malignancy by the National Cancer Center in 2010. It is the second most commonly diagnosed malignancy in men after lung cancer and in women after breast and cervical cancer.1 Median survival of stage IV CRC without any kind of treatment has been reported to be around 5 to 6 months.2, 3 The liver appears to be the most common organ of distant metastatic spread from colorectal cancer. Approximately 25% of patients present with synchronous disease and an additional 30% to 40% will develop hepatic metastases during the course of their disease.4 In addition, liver metastases are found in over 50% of patients who die from CRC and hepatic involvement is the most implicated reason for their death.5 This review will attempt to give an overview of the treatment alternatives in CRC patients with liver metastasis, with a focus on the updated rationales as well as controversial and current trends in the multidisciplinary approach.